The Effect of Irrigation Rate and Period on the Growth and Height of the "Uzbekistan 601 ESV" Hybrid of Corn - Uzakov Gulomjon Okbutaevich; Chariev Shakhbos Mardonovich (Genius Journals, 2023)
This article highlights the influence of norms and terms of irrigation on the growth and height of the corn hybrid "Uzbekistan 601 ECB" on irrigated lands in the southern region of the republic. It was found that the height of the plants was the highest (281.3 cm) in the variant with a large number and number of irrigations, and low (198.0 cm) in the variant with the least irrigation
Keywords: Corn; Uzbekistan 601 ERUs; variety; water